“The Quality of Digital Visual Arts in Light of Digital Advancements” (Comprehensive Journal of Science, 2024)
This research aims to study artistic quality in digital visual arts in light of contemporary technological development by analyzing the transformations brought about by modern technologies in the structure of the artwork, as well as in its production and reception processes, and in reshaping aesthetic and artistic evaluation standards. The study is based on the fundamental idea that digital arts are no longer merely an extension of traditional arts using modern tools, but have become an independent artistic field in which human creativity intersects with technological systems and intelligent software, leading to a redefinition of the concept of artistic quality within a changing digital context.The study focuses on analyzing the impact of technological development, including artificial intelligence, augmented reality technologies, and digital design software, in enhancing artistic production capabilities in terms of visual precision, media diversity, and enabling higher levels of interaction between the artwork and the viewer. It also discusses the transformation of the artist’s role, where it is no longer limited to direct execution, but has become a guiding role in a creative process in which algorithms and digital tools participate in generating and shaping the visual image.The research adopts a descriptive-analytical methodology through reviewing relevant literature and previous studies related to digital visual arts and technological development, as well as analyzing concepts associated with artistic quality and evaluation standards of artworks. The findings reveal that technological advancement has significantly contributed to improving artistic quality by enhancing creative capabilities, expanding experimental possibilities in art, improving visual production efficiency, and strengthening interactivity, which has become a fundamental criterion in evaluating digital artworks.The study concludes that the concept of artistic quality is no longer based solely on traditional criteria such as composition and technical skill, but has become a complex concept that includes aesthetic, technical, interactive, and semantic dimensions. This reflects the nature of digital arts as dynamic and constantly evolving forms. The research ultimately concludes that the relationship between technological development and artistic quality is a complementary one, where technological progress contributes to reshaping art itself rather than merely improving its tools, which necessitates the development of new evaluation standards for digital visual arts in line with this transformation.
Keywords: Artistic quality, digital visual arts, technological development, artificial intelligence, augmented reality, visual arts, digital creativity